2021
DOI: 10.28945/4778
|View full text |Cite
|
Sign up to set email alerts
|

The Flipped Classroom Model in Libyan Higher Education: Experiences with Students of Computer Principles

Abstract: Aim/Purpose: This study aims to examine the effectiveness of the flipped learning approach in a computer principles course at Alasmarya Islamic University, Libya. Background: The reason for this consideration was to evaluate the viability of conventional lecture-based educational programmes versus the active learning of computer concepts in flipped classrooms for college economics students at the Alasmarya Islamic University. Methodology: The experiment was applied to two groups: one, class A, undertook the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…Similarly to our findings, positive student attitudes toward flipped learning and teaching have also been confirmed by other authors (Al Ghawail & Ben Yahia, 2021;Bell, 2015;Farah, 2014;Hantla, 2014;Leo, 2017;Prefume, 2015;Tanner & Scott, 2015;Vaughn, 2014;Yang, 2017). However, the research conducted by Xiu and Thompson (2020) was inconclusive as to whether they want this type of implementation to continue in the future, similar to some other contradictory results (Hunley, 2016;L.…”
Section: More Cooperationsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly to our findings, positive student attitudes toward flipped learning and teaching have also been confirmed by other authors (Al Ghawail & Ben Yahia, 2021;Bell, 2015;Farah, 2014;Hantla, 2014;Leo, 2017;Prefume, 2015;Tanner & Scott, 2015;Vaughn, 2014;Yang, 2017). However, the research conducted by Xiu and Thompson (2020) was inconclusive as to whether they want this type of implementation to continue in the future, similar to some other contradictory results (Hunley, 2016;L.…”
Section: More Cooperationsupporting
confidence: 91%
“…It is, therefore, necessary to investigate further and possibly identify the determinants more clearly. Third, while research at the secondary and higher education level dominates (e.g., Al Ghawail & Ben Yahia, 2021;Foldnes, 2016;Lee et al, 2022;Murillo-Zamorano et al, 2019;Pastes Urbano et al, 2020;Sharp & Sharp, 2017;Sommer & Ritzhaupt, 2018;Xiu & Thompson, 2020;Yang, 2017;Yelamarthi et al, 2016), there is less research at the primary school level , which is why we have focused on this level of schooling. We were interested in comparing traditional and flipped learning and teaching from the point of view of acquired knowledge and its retention, as well as students' perceptions of flipped learning and teaching.…”
Section: Introductionmentioning
confidence: 99%
“…These results have been confirmed by some works that consider that students prefer hybrid or face-to-face teaching [23][24][25][26], flipped classroom [27][28][29], active learning methods [30,31]. Similarly, the results showed that students strongly prefer the integration of ICT in the teaching -learning process (Figure 4), and according to [32][33][34] showed that students are satisfied with the use of digital resources.…”
Section: Evaluation Of the Digital Textbooksupporting
confidence: 66%
“…This approach that contradicts with the linearity of learning and focuses on the student and make the teacher as a companion and facilitator of learning [11]. From a motivational point of view, the flipped classroom is an approach preferred by students [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%